2014
DOI: 10.4292/wjgpt.v5.i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy preparation-induced disorders in renal function and electrolytes

Abstract: Colonoscopy and flexible sigmoidoscopy are commonly used mainly for colon cancer screening and detection, but also in several other situations such as inflammatory bowel disease (for diagnosis and follow up) and gastrointestinal hemorrhage. Bowel cleansing preparations mainly include polyethylene glycol and oral sodium phosphate solutions, with the later being most frequently used due to better toleration from patients. Despite their favourable safety profile these agents have been associated with renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Bowel preparation was the same for all the patients, and none of them received oral sodium phosphate, which has been associated with AKI 12 . On the other hand, a large outpatient screening study showed that AKI risk is not associated with oral sodium phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bowel preparation was the same for all the patients, and none of them received oral sodium phosphate, which has been associated with AKI 12 . On the other hand, a large outpatient screening study showed that AKI risk is not associated with oral sodium phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation during colonoscopy may lead to hypoxemia, bradycardia, hypotension, cardiac arrhythmias, or cerebrovascular events 10 , 11 . Complications specifically related to bowel preparation include poor preparation, kidney injury and hydro-electrolyte disorders 12 - 14 . Sodium phosphate solutions for bowel preparation have been related to increased risk of acute renal failure (acute phosphate nephropathy possibly associated with hyperphosphatemia) and delayed kidney injury 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to other electrolytes, a number of abnormalities have been associated with OPS, including significant hypokalemia and hypernatremia 20 21 . These occur principally as a result of absorption of sodium present in the OPS through the intestinal epithelium in exchange for potassium when fluid intake is insufficient and intraluminal sodium concentration exceeds normal plasma levels 20 . Hypokalemia and hypernatremia are particularly frequent in the elderly 22 and, if severe, may be associated with cardiac rhythm disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…Acute phosphate nephropathy can occur even in patients with normal renal function and also in patients with preexisting renal disease, especially those who are using diuretics or angiotensin converting enzyme inhibitors. Therefore, this preparation should be avoided in these patients [ 36 , 40 ]. The FDA in the United States has issued a black box warning pertaining to the risk of acute phosphate nephropathy associated with NaP in elderly and patients with preexisting renal disease.…”
Section: Introductionmentioning
confidence: 99%